2018
DOI: 10.1088/1748-9326/aad5c5
|View full text |Cite
|
Sign up to set email alerts
|

A critical assessment of the long-term changes in the wintertime surface Arctic Oscillation and Northern Hemisphere storminess in the ERA20C reanalysis

Abstract: This study investigates the robustness of the long-term changes in the wintertime surface Arctic Oscillation (AO) in the ERA20C reanalysis. A statistically significant trend in the AO is found in ERA20C over the period 1900-2010. These long-term changes in the AO are not found in two other observational datasets. The long-term change in the AO in ERA20C is associated with statistically significant negative trend (approximately −6 hPa per century) in mean-sea level pressure (MSLP) over the Northern Hemisphere p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 53 publications
5
30
3
Order By: Relevance
“…We show that the disagreement is linked to the assimilation of marine surface winds, which is only performed in the ECMWF reanalyses. Our results have implication beyond wind applications and may explain several issues identified in previous analysis, such as reported drifts and discontinuities of ocean heat content (Laloyaux et al, 2016), trends in Arctic mean sea level pressure (MSLP; Bloomfield et al, 2018), and disagreeing long-term trends in cyclones and wind storms (Befort et al, 2016). Moreover, trends in wind speeds are expected to impact other societally relevant fields such as energy, the water cycle (McVicar et al, 2012), and food chains in the oceans (Kahru et al, 2010).…”
Section: 1029/2018jd030083mentioning
confidence: 59%
See 2 more Smart Citations
“…We show that the disagreement is linked to the assimilation of marine surface winds, which is only performed in the ECMWF reanalyses. Our results have implication beyond wind applications and may explain several issues identified in previous analysis, such as reported drifts and discontinuities of ocean heat content (Laloyaux et al, 2016), trends in Arctic mean sea level pressure (MSLP; Bloomfield et al, 2018), and disagreeing long-term trends in cyclones and wind storms (Befort et al, 2016). Moreover, trends in wind speeds are expected to impact other societally relevant fields such as energy, the water cycle (McVicar et al, 2012), and food chains in the oceans (Kahru et al, 2010).…”
Section: 1029/2018jd030083mentioning
confidence: 59%
“…The trends may be spurious and due to evolving wind measurement techniques. Moreover, Bloomfield et al () report a spurious MSLP trend over the Arctic, which hints to a disagreement between the assimilated MSLP and wind speed data. The trends also disagree with land‐based wind measurements, which feature downward trends in the last couple of decades.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This gridded product has a spatial resolution of 2°latitude × 2°longitude, and extends from 1920 to 2014. Long-term SLP trends over the NH extratropics in winter are considered more reliable in the 20CR than the ECMWF 20th Century Reanalysis (Poli et al, 2016) as documented by Bloomfield et al (2018). Long-term SLP trends over the NH extratropics in winter are considered more reliable in the 20CR than the ECMWF 20th Century Reanalysis (Poli et al, 2016) as documented by Bloomfield et al (2018).…”
Section: Observational Data Setsmentioning
confidence: 99%
“…Benchmarking a 100-year event for example is thus quite difficult and associated with very large uncertainties. As recent studies have shown there is also a spurious trend in this reanalysis data set (Befort et al, 2016;Bloomfield et al, 2018). The lack of observations is often tackled by producing probabilistic event sets based on alteration of observed events (e.g., Schwierz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%